Tungstate removal from aqueous solution by nanocrystalline iowaite: An iron-bearing layered double hydroxide. (April 2019) - Cao, Yaowu; Guo, Qinghai; Shu, Zhu; Jiao, Cong; Luo, Li; Guo, Wei; Zhao, Qian; Yin, Zuowei
Abstract: Tungstate enrichment in aquatic systems may cause negative environmental and health effects. This study addresses tungstate removal from aqueous solution by nanocrystalline iowaite, an iron-bearing layered double hydroxide, which has not been used for treatment of tungstate-rich waters so far. Tungstate sorption experiments were conducted with various contact times, temperatures, initial tungstate concentrations (0.001–2 mM), and solution pH values (2–13), the results indicating that iowaite sorbed aqueous tungstate effectively and quickly, and the sorption maximum can be up to 71.9 mg/g. Moreover, the tungsten sorption capacity keeps nearly constant at a wide pH range from 3 to 11. Duo to its pH buffering effect, the alkaline conditions were generated by the addition of iowaite, which are favorable for the removal of aqueous tungstate because the polymerization of tungstate can be prohibited at alkaline pH values. Zeta potential, XRD and XPS analyses were employed to clarify the sorption mechanisms, and it was concluded that tungstate was sorbed via its exchange with the chloride originally intercalated into iowaite interlayers as well as its stronger inner-sphere complexation with the Fe atoms located in iowaite layers. Nanocrystalline iowaite is suitable for treating both tungstate-bearing natural waters with moderately high tungstate concentrations and industrial wastewaters extremely rich in tungstate. Graphical abstract: Image 1 Highlights: Tungsten sorbs strongly and quickly on nanocrystalline iowaite. The polymerization of tungstate is limited due to the addition of iowaite. The mechanisms for W removal include both anion exchange and surface complexation. Nanocrystalline iowaite is promising for treatment of high tungsten water.